INTRUSION ARC IN ORTHODONTIC: : CONCEPTS AND UPDATES - Liz da Cruz, Mirna; Alves Paiva, Glaucia; S. Mendes de Castro, Angelita (Health and Society, 2021)
The intrusion arch is a device for orthodontic anterior teeth intrusion, having been introduced by Burstone in 1977 for the treatment of deep bite, especially in the case of Class II division 2. But they are based on the origin of malocclusion and the patient’s clinical characteristics, such as smile line, vertical dimension, predicted growth, among others. Use of this arc is governed by the principles of mechanical intrusion, which include obtaining a pure no intrusion proclination movements, therefore, necessary for successful treatment. Among these we can highlight to get a constant magnitude of force and the choice of point of application of force in the anterior segment, which would determine whether the motion would be pure intrusion or intrusion inclined. The mechanical stability of this is making it more advantageous in the treatment of deep bite in relation to treatment with extrusion of posterior teeth, which is notoriously prone to relapse. Thus, based on the principles of mechanics and its stability, several authors have developed some type of intrusion arches, using the original biomechanics, but differing mainly in the type of alloy wire and the point of application of force to the center of resistance to achieve the goals of the treatment